Zakat and SDGs: Impact Zakat on Human Development in the Five States of Malaysia - Eko Suprayitno; Mohamed Aslam; Azhar Harun (International Journal of Zakat, 2017)
Zakat is intended to stimulate economic development, education, social, human resources empowerment, religion health, and insurance programs. The seven programs above are implemented by the Malaysian government to improve economic growth. The aim of the study is to examine the impact zakat on human development program in Malaysia using the Autoregressive Distributed Lag (ARDL) bound testing approach. The analysis was carried out for the period from 1980–2009. The finding of the research reveals that zakat has a positive and significant influence on human development in five state in the short and long run. Zakat in Malaysia can be used as tool of fiscal policy that is decided in the states of Malaysia to stimulate human development and economic growth in the long run. Keyword: Zakat, Human Development, Granger causality test